Utilization of the Topsis Method in Determining Operationally Worthy Vehicles at the Tirtanadi PDAM Office, North Sumatra Province - Yulia Agustina Dalimunthe; Hasdiana Hasdiana; Zulham Efendi Van Batubara; Dedi Irwan (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2023)
PDAM Tirtanadi Sumut provides a supporting facility, one of which is operations that are used in carrying out daily employee activities. The problem has occurred that many operational vehicle are no longer suitable for use because the age of the vehicle is long. the cost of spare parts that are increasingly being replaced makes the company have to spend quite a lot of money to buy spare parts and repair the operational vehicle. The purpose of this study is to assist PDAM Tirtandi, North Sumatra Province in determining suitable cars to use using the Topsis method (Technique For Order Preference By Similarity To Ideal Solution) and it is hoped that this method will be able to determine suitable operational vehicles at the North Sumatra Province PDAM office.